The effect of gender imbalance on housing price in China - Han, Xinping; Wan Ngah, Wan Azman Saini; Rosland, Anitha; Bani, Yasmin; Law, Siong Hook (Korea Distribution Science Association, 2021)
House ownership is considered as one of the important pre-conditions for marriage in China. Given that gender imbalance is a prominent issue in the country, competition for marriage partners might motivate males to look for a house and probably bigger and more expensive house. This is believed to have caused house price hikes in recent years. This study aims to investigate the impact of gender imbalance on house prices using data from 30 provinces in China for the 2000-2017 period. The results based on the generalized method of moments (GMM) estimations show that house price is strongly influenced by gender imbalance. However, there is no evidence to support differential effects across eastern and mid-western regions. One potential reason is that pre-marriage house ownership has become a common culture for the whole community and therefore it does not vary significantly across regions. There are several important policy implications. Firstly, the issues should be addressed by the policymakers at national level and not regional level. Secondly, the government should intervene to bring back gender ratio to its normal level. Finally, the government should limit the number of houses people can buy and increase the supply of houses in the market.